2006
DOI: 10.1038/sj.leu.2404413
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and biological implications of genetic abnormalities in multiple myeloma undergoing autologous stem cell transplantation: t(4;14) is the most relevant adverse prognostic factor, whereas RB deletion as a unique abnormality is not associated with adverse prognosis

Abstract: Fluorescence in situ hybridization (FISH) has become a powerful technique for prognostic assessment in multiple myeloma (MM). However, the existence of associations between cytogenetic abnormalities compels us to re-assess the value of each abnormality. A total of 260 patients with MM at the time of diagnosis, enrolled in the GEM-2000 Spanish transplant protocol, have been analyzed by FISH in order to ascertain the independent influence on myeloma prognosis of IGH translocations, as well as RB and P53 deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 29 publications
8
116
3
1
Order By: Relevance
“…20 The FISH results of all the patients included in the present study have been previously reported. 12 Statistical analyses SPSS version 15.0 (SPSS Inc., Armonk, NY, USA) was used for statistical analysis.…”
Section: Cytogenetic Analysesmentioning
confidence: 88%
See 1 more Smart Citation
“…20 The FISH results of all the patients included in the present study have been previously reported. 12 Statistical analyses SPSS version 15.0 (SPSS Inc., Armonk, NY, USA) was used for statistical analysis.…”
Section: Cytogenetic Analysesmentioning
confidence: 88%
“…The only five cases with no CNA were from asymptomatic entities (two MGUS and three SMM patients), whereas all MM patients showed at least one CNA. Overall, a total of 703 DNA copy number changes were detected with a median of 8 imbalances per abnormal case (range, 1-32 imbalances): 374 gains with a median of 4 per abnormal case (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and 329 losses with a median of 3 (range . A detailed description of the most frequent aberrations is shown in Supplementary Table 2.…”
Section: Quality Assessment Of Snp Arraysmentioning
confidence: 99%
“…Cell culture plates were incubated in a cell culture incubator at 37 1C until the extent of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT; Sigma-Aldrich) reduction in each well was quantified. Inhibitory concentration 50% (IC 50 ) is defined in this context as the drug concentration that causes the cells to proliferate at a rate that is half as rapid as cells incubated in the absence of drugs. 18,39,40 Western blot analysis Cells were cultured and then protein lysates prepared as described.…”
Section: Analysis Of Cell Sensitivity To Anticancer Agentsmentioning
confidence: 99%
“…Although still useful, conventional prognostic factors (β 2 -microglobulin, lactate dehydrogenase, serum albumin, Creactive protein, etc) 5 appear to be somewhat less discerning of the outcome compared with the genetic aberrations that drive the tumor biology. [6][7][8][9][10] The Mayo Stratification of Myeloma and Risk-Adapted Therapy (mSMART) criteria use a combination of metaphase CG, FISH, and plasma cell labeling index (PCLI; a measure of the percentage of plasma cells in the S phase of the cell cycle) 11 results to derive 2 composite risk categories (high-risk vs standard-risk) for prognostication of patients with newly diagnosed MM. 12 Although the initial prognostication criteria were based on the evidence predominantly garnered from patients treated with conventional chemotherapy and/or stem cell transplantation (SCT), the recommendations are periodically revised as new data emerge.…”
mentioning
confidence: 99%